Значењето на јавниот простор за функционирањето и развојот на Европската Унија и за напредокот на европските интеграции на Република Северна Македонија - Ајдари, Рина (Филозофски факултет, УКИМ, Скопје, 2022)
This study attempts to present a theoretical development of the main lines of research related to the emergence of the European public sphere, within the European Union. Since the mid-1990s, research in the European public sphere has increased. The interest in this issue should be understood in the context of the discussions on the European democratic deficit and, above all, in relation to the question of the existence and / or desirability of a single European demos and a common European identity. In general, the European public sphere is seen and perceived as a means of increasing the legitimacy of EU policy and the democratization of the EU. The research focuses on the questions: whether and to what extent the European public sphere exists and functions; and whether it is being formed at European or national level; at the same time, it aims to operationalize concepts such as: communication across national borders; creation of the so-called European communication structures; and Europeanization of national public spheres. The research provides an analysis of who are the main actors that create it and which practically contribute to the functionality of the European public sphere (political parties, media, think tanks and NGOs); how they affect the process of EU enlargement and the process of integration of the Republic of North Macedonia in the EU through the creation of internal communication networks and structures.
Докторска дисертација одбранета во 2022 година на Филозофскиот факултет во Скопје, под менторство на проф. д–р Милева Ѓуровска.
Keywords: public opinion; public sphere; Europeanization; European Union, North Macedonia